Pareto-improving toll adjustment for a buildoperate-transfer toll road project with unknown demand - Tan, Zhijia; Tan, Wei (European Journal of Transport and Infrastructure Research, 2014)
The social welfare gain and investment return are two main concerns of a road investment project, and they are usually key components of a Build-operate-transfer (BOT) contract. Therefore, the Pareto efficient outcomes of the two objectives are attractive for both government and private investor. This paper proposes a ex-post toll adjustment procedure called Paretoimproving trial-and-error procedure (PI-TEP), in order to achieve the Pareto efficient outcomes for a BOT toll road project with pre-determined road capacity and unknown demand function. The PI-TEP is novel and Pareto-improving, since the procedure does not require an analytical demand function and can improve social welfare and revenue simultaneously. Furthermore, the PI-TEP is theoretically proved to be efficient in obtaining the Pareto efficient outcomes. And thus, the procedure is practically useful and valuable for both government and private investor in a BOT toll road project.